Development of Augmented Reality Card Media to Increase Interest and Cognitive Learning Mathematics in the Elementary Schools - Millah, Hidayatul; Sulianto, Joko; Kiswoyo (LPPM Universitas PGRI Semarang, 2025)
This research is motivated by students who tend to be easily bored, and do not understand mathematics learning material on the material of building space. This happens because of the lack of teacher's ability to use appropriate and concrete learning media in classroom learning. There are still many teachers who use the pictures available in the book only for the material of building space, so that many students do not understand the material of building space taught. Thus, the purpose of this study is to analyze the needs, design, develop technology-based learning media, especially Augmented Reality-based media cards by conducting feasibility tests evaluated by experts, improving student understanding and knowing feedback from users. The research method used is Reseacrh and Development (R&D) by applying the ADDIE procedure which consists of five stages, namely analysis, design, development, implementation and evaluation. Based on the research results, the media feasibility evaluation obtained an average of 93,26%. This product trial was conducted at SDN Sawah Besar 01 by conducting three meetings, namely pretest, treatment, and posttest. Based on the results of the cognitive understanding test, it shows that there is an increase in student understanding by using Augmented Reality-based Card media in learning. Augmented Reality-based Card media also received positive responses by students through student response questionnaires.